2014
DOI: 10.1021/ac501412c
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Based Biosensor to Report DNA Damage in Micro- and Nanosystems

Abstract: Understanding how newly engineered micro- and nanoscale materials and systems that interact with cells impact cell physiology is crucial for the development and ultimate adoption of such technologies. Reports regarding the genotoxic impact of forces applied to cells in such systems that can both directly or indirectly damage DNA emphasize the need for developing facile methods to assess how materials and technologies affect cell physiology. To address this need we have developed a TurboRFP-based DNA damage rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 57 publications
(127 reference statements)
0
13
0
Order By: Relevance
“…Although particularly fast-maturing and bright variants of fluorescent proteins (TurboGFP/RFP) were used, it seems likely that the accumulation time still exceeded the time needed to produce detectable amounts of luciferase since the fluorescent proteins lack the multiplication effect of Luc that is active as an enzyme. Consistent with this, assessment of fluorescent reporter expression is typically performed after exposure for 12 hours and longer [ 15 , 17 ]. Furthermore, the vector for luciferase differed from the ones used for the fluorescent proteins, which can also influence responsiveness, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although particularly fast-maturing and bright variants of fluorescent proteins (TurboGFP/RFP) were used, it seems likely that the accumulation time still exceeded the time needed to produce detectable amounts of luciferase since the fluorescent proteins lack the multiplication effect of Luc that is active as an enzyme. Consistent with this, assessment of fluorescent reporter expression is typically performed after exposure for 12 hours and longer [ 15 , 17 ]. Furthermore, the vector for luciferase differed from the ones used for the fluorescent proteins, which can also influence responsiveness, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies using reporter constructs, such as for markers of DNA damage and oxidative stress [ 15 , 16 ], were mostly validated indirectly, e.g. by comet assay or ROS measurements, rather than a specific assessment of the actual gene of interest by several endpoints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rider et al reported the first cell sensor that used B lymphocytes to recognize specific bacteria with the help of membrane-bound IgM antibodies32. Mammalian cell-based biosensors have a distinct advantage in reflecting cellular physiological action rather than just quantitative detection and therefore can provide insight into mechanism of action of analytes333435. More importantly, tests based on human cells rather than other cell types, are more likely to detect contaminants that can cause adverse effects in humans.…”
mentioning
confidence: 99%
“…Though prior work has examined the gross effects (e.g., viability, proliferation) of analytes on cells313637, these gross assays do not reveal more subtle effects that mask or alter particular phenotypes of interest, such as the activation of signaling pathways. Recently, methods based on the reporting of analytes by fluorescence reaction in engineered cells offer a simple and nondestructive option33343538. Living cells used as biosensors are typically produced with a constructed plasmid, in which genes that code for the bio-reporter are placed under control of a promoter that recognizes the analyte of interest.…”
mentioning
confidence: 99%